Breeding for Sclerotinia Blight Resistance on Peanut in the U.S.: A Review - Kelly D. Chamberlin; Rebecca S. Bennett; Maira Rodrigues Duffeck (Agronomy)
Sclerotinia blight is one of the most widespread and economically damaging diseases of peanut (Arachis hypogaea L.), causing significant crop losses in cooler production areas across the world. In the U.S., Sclerotinia blight caused by Sclerotinia minor has been an issue for producers for over 50 years and remains troublesome with regards to inheritance of resistance, management strategies, and resistant germplasm sources. This review provides an overview of the disease on peanut, progress towards the identification of genomic regions responsible for resistance, and the development of resistant cultivars in the U.S.